Analisis Kinerja Keuangan Koperasi Pegawai Republik Indonesia (KPRI) Gelora Pendidikan Tomohon - Thesar Ponamon; Olviane Sumampouw; Michel Potolau (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to find out how the financial performance of the (KPRI) Tomohohn Education Center using financial ratio analysis. The population used is the cooperative financial report with samples from 2015 to 2017. The method of data analysis used is the analysis of quantitative descriptive data that is examined using financial ratio analysis. The results of this study are that the current ratio 2015 is 213%, 2016 is 198%, 2017 is 205%, the debt to equity ratio 2015 is 46.75%, 2016 is 50.50%, 2017 is 48 , 70%, and return on assets 2015 at 9.21%, 2016 at 8.38%, 2017 at 7.26%. From the results of the ratio calculation it can be concluded that the Current Ratio, Debt to Asset Ratio (KPRI) Tomohon Education Center generally shows very good criteria, and Return on Assets in criteria is not very good